What is influencing the dropout behaviour of youth players from organised football? A systematised review - Schlesinger, T.; Löbig, A.; Enhold, P.; Nagel, S. (German Journal of Exercise and Sport Research, 2018)
This article provides a systematised review of relevant factors influencing youth dropout from organised football. The findings of identified 30 studies concerning dropout behaviour in football indicate the multidimensional influences of intrapersonal, interpersonal and structural factors. Most studies investigate the influence of intrapersonal factors. Accordingly, negatively perceived football competence, lack of motivation, goals and incentives and a lower relative age lead to a higher dropout rate. At the interpersonal level, lack of support from significant others (parents, peers, coach) and a disadvantageous team situations promote withdrawal from organised youth football. A lack of organisational and structural conditions promote dropout too. Based on this review, the following identified research gaps should be addressed in future studies: (1) analysis of individuals` dropout decision as a selection of available alternatives, (2) referencing to corresponding contextual features of dropout behaviour, (3) the longitudinal perspective at dropout behaviour and (4) the perspective of intervention. Furthermore, some practical implications can be derived for the management of youth members in football clubs: (1) strengthen and develop successive coaching competencies, (2) reflection of own club philosophy against the background of divergent expectations of adolescents, (3) measures to promote identification with the football club and (4) anchoring of orientation regarding to young players as a central objective in the club. Dieser Beitrag bietet eine systematisierte Übersicht zu relevanten Faktoren, die den Ausstieg (Drop-out) von Jugendlichen aus dem vereinsorganisierten Fußball beeinflussen. Die Ergebnisse von 30 identifizierten Studien zum Thema Drop-out-Verhalten im Fußball verweisen auf multidimensionale Einflüsse intrapersonaler, interaktionaler und struktureller Faktoren. Die meisten Studien untersuchen dabei den Einfluss intrapersonaler Faktoren. So erhöhen negativ wahrgenommene Fußballkompetenzen, mangelnde Motivation, Ziele und Anreize sowie ein relativer Alterseffekt die Wahrscheinlichkeit eines Drop-outs. Auf der interaktionalen Ebene befördern mangelnde Unterstützung (von Eltern, Peers und Trainern) sowie Probleme innerhalb der Mannschaft den Ausstieg aus dem organisierten Jugendfußball. Unzureichende organisatorische und strukturelle Bedingungen beeinflussen ebenfalls das Drop-out-Verhalten. Basierend auf dieser Analyse sind folgende identifizierte Forschungslücken in zukünftigen Studien zu berücksichtigen: 1. Analyse der Drop-out-Entscheidung als Selektion verfügbarer Alternativen; 2. Bezugnahme auf zugrunde liegende Kontextbedingungen des Drop-out-Verhaltens; 3. Verlauf des Drop-out-Verhaltens sowie 4. Interventionsperspektiven. Darüber hinaus können praktische Konsequenzen für das Management von Jugendlichen in Fußballvereinen abgeleitet werden: 1. Stärkung und Entwicklung altersgerechter Trainerkompetenzen; 2. Reflexion der eigenen Vereinsphilosophie vor dem Hintergrund divergierender Erwartungen von Jugendlichen; 3. Maßnahmen zur Förderung der Identifikation mit dem Fußballverein und 4. Verankerung des Themas Förderung von Jugendlichen als zentrales Vereinsziel.